PENGARUH KENYAMANAN, KELENGKAPAN PRODUK DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SWALAYAN KOPERTA LANGGENG MULYO - Ulfa, Aisyah Nur Ulia; Listyani, Indah; Swasono, Edy; Mu’arrofah, Afrila (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to determine the effect of comfort, product completeness and price on consumer purchasing decisions at the Koperta Langgeng Mulyo Ngancar Kediri Supermarkets. In this study the population was 765 consumers. The sample is 79 respondents. Typical accidental sampling sampling. Data analysis techniques used in this study were to use the validity and reliability test, multiple linear regression test and hypothesis testing through SPSS. Based on the analysis conducted, the results of the study are obtained: (1) Empirically proven that comfort has no effect on purchasing decisions. (2) Empirically proven the completeness of the product partially influences the purchasing decision. (3) Empirically proven that prices have a partial effect on consumer purchasing decisions. (4) Empirically proven that comfort, completeness of products and prices simultaneously influence the purchase decision.